2002
DOI: 10.1258/0956462021925126
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk factors among patients with tuberculosis — Botswana 1999

Abstract: To identify factors associated with HIV in Botswana, a standardized questionnaire was administered to 135 tuberculosis patients with known HIV status. HIV-positive patients were more likely than HIV-negative patients to: be female (45% vs 26% (adjusted prevalence odds ratio (aPOR)=3.8, 95% confidence interval (CI)=1.1-12.7)); be 26-35 years old (50% vs 19% (aPOR=2.7, CI=0.7-10.7)); be unmarried (91% vs 71% (aPOR=13.3, CI=2.5-72.7)); have higher income (24% vs 10% (aPOR=8.2, CI=1.6-42.9)); report separation fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 8 publications
7
22
0
Order By: Relevance
“…Of the 20 studies included in Fisher and colleagues' meta-analysis, 19 were retained for inclusion in the present study (Ao, Sam, Masenga, Seage, & Kapiga, 2006;Ayisi et al, 2000;Braddick et al, 1990;Demissie, Amre, & Tsega, 1996;Fritz et al, 2002;Hargreaves et al, 2002;Kapiga, Lyamuya, Lwihula, & Hunter, 1998;Kapiga et al, 2002;Kapiga et al, 2006;Lewis et al, 2005;Mbulaiteye et al, 2000;Mnyika, Klepp, Kvåle, & Ole-King'ori, 1996;Ndina-Achola et al, 1997;Sebit et al, 2003;Simbayi et al, 2004;Talbot et al, 2002;Tengia-Kessey, Msamanga, & Moshino, 1998;Zablotska et al, 2006;Zuma, Gouws, Williams, & Lurie, 2003) and one (Gilgen, Williams, & Campbell, 2000) was excluded for failing to meet the inclusion criteria specified below (i.e., it was not published in a peer-reviewed journal). An additional eight nonoverlapping studies published prior to 2009 were identified from our previous narrative review (Allen et al, 1992;Bassett et al, 1996;Clift et al, 2003;Dunkle et al, 2004;Fisher, Cook, Sam, & Kapiga, 2008;Msuya et al, 2006;St.…”
Section: Methods Literature Reviewmentioning
confidence: 99%
“…Of the 20 studies included in Fisher and colleagues' meta-analysis, 19 were retained for inclusion in the present study (Ao, Sam, Masenga, Seage, & Kapiga, 2006;Ayisi et al, 2000;Braddick et al, 1990;Demissie, Amre, & Tsega, 1996;Fritz et al, 2002;Hargreaves et al, 2002;Kapiga, Lyamuya, Lwihula, & Hunter, 1998;Kapiga et al, 2002;Kapiga et al, 2006;Lewis et al, 2005;Mbulaiteye et al, 2000;Mnyika, Klepp, Kvåle, & Ole-King'ori, 1996;Ndina-Achola et al, 1997;Sebit et al, 2003;Simbayi et al, 2004;Talbot et al, 2002;Tengia-Kessey, Msamanga, & Moshino, 1998;Zablotska et al, 2006;Zuma, Gouws, Williams, & Lurie, 2003) and one (Gilgen, Williams, & Campbell, 2000) was excluded for failing to meet the inclusion criteria specified below (i.e., it was not published in a peer-reviewed journal). An additional eight nonoverlapping studies published prior to 2009 were identified from our previous narrative review (Allen et al, 1992;Bassett et al, 1996;Clift et al, 2003;Dunkle et al, 2004;Fisher, Cook, Sam, & Kapiga, 2008;Msuya et al, 2006;St.…”
Section: Methods Literature Reviewmentioning
confidence: 99%
“…A study among TB patients found the use of alcohol before sex by either the respondent or their sex partner was significantly associated with being HIV+ (Talbot et al, 2002). In contrast, another study conducted among men and women receiving STI clinic services found no significant difference in HIV prevalence between those who had or had not used alcohol in sexual contexts in the previous month (Simbayi et al, 2004).…”
Section: Original Articlementioning
confidence: 98%
“…To identify risk factors associated with HIV, an unmatched case-control study in Gaborone, Botswana, was conducted between 1 May and 1 December 1999 among 135 tuberculosis (TB) patients whose HIV status was known (Talbot et al, 2002).…”
Section: Clinic/health Facility Attendeesmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies have confirmed TB transmission by coinfected individuals (24)(25)(26). However, given the large population of people with HIV and TB, it is unclear whether ongoing transmission of TB is more likely attributed to HIV-infected patients with TB or their seronegative counterparts.…”
Section: Epidemiologymentioning
confidence: 99%